Occurrence of Diplostomum pseudospathaceum Niewiadomska, 1984 and D. mergi Dubois, 1932 (Digenea: Diplostomidae) in Danish freshwater snails: ecological and molecular data - Haarder, Simon; Jørgensen, Kasper; Kania, Per Walter; Skovgaard, Alf; Buchmann, Kurt (Folia parasitologica, 2013)
Freshwater pulmonate snails from three locations in Lake Furesø north of Copenhagen were screened for infection with furcocercariae (by shedding in the laboratory) and recovered parasite larvae were diagnosed by molecular methods (by performing PCR of rDNA and sequencing the internal transcribed spacer [ITS] region). Overall prevalence of infection in snails was 2%. Recovered cercariae from Lymnaea stagnalis (Linnaeus) were diagnosed as Diplostomum pseudospathaceum Niewiadomska, 1984 (prevalence 4%) and cercariae from Radix balthica (Linnaeus) as D. mergi (Dubois, 1932) (prevalence 2%). Pathogen-free rainbow trout were then exposed to isolated cercariae and infection success and site location of metacercariae in these fish were determined. Infection experiments confirmed that both species could infect rainbow trout with the eye lens as infection site for the metacercarial stage although infection success differed. Combination of molecular and biological assays may contribute to improvement of our knowledge on diagnosis, distribution and biology of diplostomids in fish.
Keywords: sladká voda; hlemýždi; fylogeneze; ryby; Specific Pathogen-Free Organisms; roční období; Molecular Sequence Data; Seasons; Fish Diseases; Base Sequence; Ecology; Snails; nemoci ryb; metacerkárie; Animals; Fishes; Metacercariae; Oncorhynchus mykiss; Sequence Analysis, DNA; zvířata; DNA, Ribosomal Spacer; jezera; polymerázová řetězová reakce; infekce červy třídy Trematoda; Fresh Water; sekvence nukleotidů; Lakes; Polymerase Chain Reaction; Trematode Infections; Phylogeny; organismy bez specifických patogenů; Trematoda; Dánsko; sekvenční analýza DNA; mezerníky ribozomální DNA; Denmark; ekologie; molekulární sekvence - údaje